In vitro effects of purified lacticin from whey isolated Lactococcus lactis culture on Staphylococcus aureus and MCF-7 breast cancer cells - Mahtab Hosseinzadeh‎; Monir Doudi; Ali Mohammad Ahadi (Iranian Journal of Microbiology)
Background and Objectives: Bacteriocins are interested as antibacterial and anticancer agents due to their high specificity and low side effects. This study aimed to isolate bacteria which produce bacteriocins of the lacticin family from whey and to investigate their antibacterial and anticancer effects. Materials and Methods: Lactic acid bacteria were isolated from different whey samples. The presence of the lacticin gene in the isolates was checked using PCR and then the inhibitory effects of their bacteriocin was investigated on Staphylococcus aureus utilizing well plate method. The protein content was separated by dialysis. The presence of lacticin was checked with the help of SDS-PAGE. The lacticin producing bacterium was identified through the sequencing of the 16S rRNA gene. Finally, the cytotoxicity of the obtained protein was studied on the MCF-7 breast cancer cells using MTT and scratching tests. Results: The isolated lacticin-producing Lactococcus lactis was able to grow in acidic conditions (pH = 2.5 for 3 h) and in bile salts (0.3% for 24 h). The bacterium produced 4.2 μg/μl bacteriocin with a molecular weight of 3.1 KD. The lacticin showed antibacterial effect against S. aureus. The cancerous cells treated with lacticin had slower growth than the control in Scratch test. Based on the MTT results, more than 80% of cancerous cells were inhibited at a concentration of 7 μg/ml lacticin with IC50 = 5.2 μg/ml. Conclusion: The bacteriocin produced in this study is a promising antibacterial and anticancer agent.